2019
DOI: 10.1021/acsenergylett.9b01539
|View full text |Cite
|
Sign up to set email alerts
|

Facile-Effective Hole-Transporting Materials Based on Dibenzo[a,c]carbazole: The Key Role of Linkage Position to Photovoltaic Performance of Perovskite Solar Cells

Abstract: The film morphology of the hole-transporting layer is proved to be the key element to charge transfer and the interfacial property in perovskite solar cells. In this Letter, a new dibenzo[a,c]carbazole (DBC) core with multiple reaction sites has been formed with a Y-shape, in which the phenanthrene group was integrated as a plane π structure into the common carbazole moiety. Accordingly, three DBC-based hole-transporting materials (HTMs) with varied molecular configurations were synthesized by the introduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 56 publications
0
35
0
Order By: Relevance
“…Thus, with the aim to optimize molecular packing of core unit, one phenyl group in Cz was replaced by phenanthrene to form dibenzo[ a , c ]carbazole (DBC) core with an extended conjugated system. The compact packing of DBC with the decreased distance between adjacent molecules was obtained by our group [ 38 ] (Figure 1), resulting in the improved photovoltaic performance of DBC‐based HTMs. Based on the previous work, further extension of conjugation core was conducted by the combination of another phenanthrene into DBC to form the tetrabenzo[ a , c , g , i ]carbazole (TBC) core (Figure 1).…”
Section: Introductionmentioning
confidence: 90%
“…Thus, with the aim to optimize molecular packing of core unit, one phenyl group in Cz was replaced by phenanthrene to form dibenzo[ a , c ]carbazole (DBC) core with an extended conjugated system. The compact packing of DBC with the decreased distance between adjacent molecules was obtained by our group [ 38 ] (Figure 1), resulting in the improved photovoltaic performance of DBC‐based HTMs. Based on the previous work, further extension of conjugation core was conducted by the combination of another phenanthrene into DBC to form the tetrabenzo[ a , c , g , i ]carbazole (TBC) core (Figure 1).…”
Section: Introductionmentioning
confidence: 90%
“…Up to now, the reported polycyclic cores can be grouped into four types according to their fused degree, namely tetracyclic, [121][122][123] pentacyclic, [124][125][126][127][128][129][130][131][132] hexacyclic, [133] and heptacyclic cores (Figure 9). [134][135][136] There are two kinds of structures for tetracyclic cores, fluoranthene and benzotrithiophene (BTT).…”
Section: Polycyclic Coresmentioning
confidence: 99%
“…In contrast to tetracyclic cores, the pentacyclic ones had a much bigger family of efficient SM-HTMs in hand. [124][125][126][127][128][129][130][131][132] The first efficient HTMs is from Jang et al [124] in 2018, where di(1-benzothieno)[3,2-b:2′,3′-d]pyrrole (DBTP) was chosen as the core and meta-methoxy revised DPA as the arms to form the molecule mDPA-DBTP. The molecule adopted a face-on orientation in the solid state, and together with the high planarity of the fused DBTP core that endowed the molecule with a strengthened intermolecular π-π stacking, a correspondingly very high hole mobility of 6.34 × 10 −4 cm 2 V −1 s −1 was obtained, superior to the value of doped spiro-OMeTAD The TPV spectra and intensity-modulated photocurrent/photovoltage (IMPS/IMVS) analyses confirmed that mDPA-DBTP presented a shorter charge extraction time and a longer charge recombination time than doped spiro-OMeTAD, suggesting better hole extraction and recombination suppression abilities.…”
Section: Polycyclic Coresmentioning
confidence: 99%
“…Recently, Liu et al reported novel design of integrated carbazole into biphenyl group and a new dibenzo[a,c]‐carbazole (DBC) core was created. [ 53 ] Consequently, three DBC‐based HTMs with different peripheral donor groups applied in mixed typical PSCs devices. Among the Y‐shaped structure, DBC‐2 contains π‐extended phenanthrene group with the twisted and C 12 linkage peripheral positions.…”
Section: Chemically Doped Hole Transporting Materialsmentioning
confidence: 99%